Respuesta :

Answer:

[tex]y = \frac{1}{2}x+\frac{7}{2}[/tex]

[tex]y = \frac{1}{2}x-\frac{1}{2}[/tex]

Step-by-step explanation:

The first step is obtain the derivative of the function y:

[tex]\frac{dy}{dx}=\frac{(x+1)*(1)-(x-1)*1}{(x+1)^{2} }=\frac{2}{(x+1)^{2} }[/tex]

(Remember that the slope of the tangent line to any curve is given by its derivative).

Secondly, in order to obtain the equations of the tangent lines parallel to x - 2y = 5 we need to obtain the slope of this line, remember that the line equation is given by:

[tex]y = mx + b[/tex]

m : slope

b: y-intercept

Then, the slope of the line

[tex]y = \frac{1}{2}x-\frac{5}{2}[/tex]

is m = 1/2.

Then, the derivative of the function y must be 1/2:

[tex]y= \frac{2}{(x+1)^{2}}=\frac{1}{2}\\(x+1)^{2}=4\\x^{2}+2x-3=0\\ (x+3)(x-1)=0\\x = -3\\x=1[/tex]

When x = -3, y =(-3-1)/(-3+1)= 2, then one of the tangent lines must pass through the point (-3,2).

When x = 1, y = (1-1)(1+1)= 0, then the other tangent line must pass through the point (1, 0).

Finally, the point-slope equation of a line is given by:

[tex]y- y_{1}  = m(x - x_{1})[/tex]

Substituting our previous results we have the equations of the tangent lines:

[tex]y - 2 = \frac{1}{2}(x - (-3))\\ y = \frac{1}{2}x+\frac{7}{2}[/tex]

[tex]y - 0 = \frac{1}{2}(x- 1) \\y = \frac{1}{2}x-\frac{1}{2}[/tex]